Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/imr.12933
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B cells: TIM‐1, transplant tolerance, and rejection

Abstract: Regulatory B cells (Bregs) ameliorate autoimmune disease and prevent allograft rejection. Conversely, they hinder effective clearance of pathogens and malignancies. Breg activity is mainly attributed to IL‐10 expression, but also utilizes additional regulatory mechanisms such as TGF‐β, FasL, IL‐35, and TIGIT. Although Bregs are present in various subsets defined by phenotypic markers (including canonical B cell subsets), our understanding of Bregs has been limited by the lack of a broadly inclusive and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 110 publications
0
50
0
2
Order By: Relevance
“…In recent years, more and more researchers have noticed a new subset of B cells that secrete IL-10 more e ciently, TIM-1 + B cells. Examination of TIM-1 + B cells revealed a 20-to 25-fold enrichment for IL-10 compared to TIM-1 − B cells [9]. TIM-1 binds to phosphatidylserine, which is ipped to the outer lea et of apoptotic cell membranes, conveying phagocytosis by macrophages and IL-10 expression by B cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In recent years, more and more researchers have noticed a new subset of B cells that secrete IL-10 more e ciently, TIM-1 + B cells. Examination of TIM-1 + B cells revealed a 20-to 25-fold enrichment for IL-10 compared to TIM-1 − B cells [9]. TIM-1 binds to phosphatidylserine, which is ipped to the outer lea et of apoptotic cell membranes, conveying phagocytosis by macrophages and IL-10 expression by B cells.…”
Section: Discussionmentioning
confidence: 97%
“…TIM-1 binds to phosphatidylserine, which is ipped to the outer lea et of apoptotic cell membranes, conveying phagocytosis by macrophages and IL-10 expression by B cells. Therefore, some researchers suggest that TIM-1 is one of the markers for the identi cation of Breg subset [9,22]. Studies have shown that mouse TIM-1 + B cells can suppress Th1 response in vivo and promote Th2 and Treg responses in an allograft transplantation setting [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deciphering B cell function within tissues is complicated by the lack of transcriptionally encoded distinction between regulatory and pathogenic cells. Although B cells can be divided into B1 (innate-like) and B2 (adaptive) subsets, both populations have the capacity to give rise to IL-10eproducing cells (Cherukuri et al, 2021). Furthermore, no driving transcription factor akin to Foxp3 for regulatory T cells has been identified.…”
mentioning
confidence: 99%
“…Furthermore, no driving transcription factor akin to Foxp3 for regulatory T cells has been identified. Instead, Bregs likely arise owing to contextually dependent differentiation and recruitment signals (Cherukuri et al, 2021;Rosser and Mauri, 2015).…”
mentioning
confidence: 99%